Priorities and preferences for school-based mental health services in India: a multi-stakeholder study with adolescents, parents, school staff, and mental health providers. (2019) - Parikh, R.; Michelson, D.; Sapru, M.; Sahu, R.; Singh, A.; Cuijpers, P.; Patel, V.
Abstract : Background: Schools are important settings for increasing reach and uptake of adolescent mental health interventions. There is limited consensus on the focus and content of school-based mental health services (SBMHSs), particularly in low-resource settings. This study elicited the views of diverse stakeholders in two urban settings in India about their priorities and preferences for SBMHSs. Methods: We completed semi-structured interviews and focus group discussions with adolescents ( n = 191), parents ( n = 9), teachers ( n = 78), school counsellors ( n = 15), clinical psychologists/psychiatrists ( n = 7) in two urban sites in India (Delhi and Goa). Qualitative data were obtained on prioritized outcomes, preferred content and delivery methods, and indicated barriers. Results: All stakeholders indicated the need for and acceptability of SBMHSs. Adolescents prioritized resolution of life problems and exhibited a preference for practical guidance. Parents and teachers emphasized functional outcomes and preferred to be involved in interventions. In contrast, adolescents' favored limited involvement from parents and teachers, was related to widespread concerns about confidentiality. Face-to-face counselling was deemed to be the most acceptable delivery format; self-help was less frequently endorsed but was relatively more acceptable if blended with guidance or delivered using digital technology. Structured sensitization was recommended to promote adolescent's engagement. Providers endorsed a stepped care approach to address different levels of mental health need among adolescents. Conclusion: SBMHSs are desired by adolescents and adult stakeholders in this setting where few such services exist. Sensitization activities are required to support implementation. School counsellors have an important role in identifying and treating adolescents with different levels of mental health needs, and a suite of interventions is needed to target these needs effectively and efficiently.